Pharmacoepidemiological profile of patients with mellitus type 1 diabetes (Research, Society and Development, 2020)
Diabetes Mellitus is an important health problem that affects millions of people in Brazil and worldwide. The type Diabetes Mellitus 1 is a predominantly autoimmune pathology, where pancreatic ß cells are progressively destroyed, resulting in absolute insulin deficiency. This study aims to quantitatively describe the pharmacoepidemiological profile of patients with DM1 treated by the specialized pharmaceutical assistance component (CEAF) in Piauí. The research was carried out at CEAF / SESAPI, through a data survey carried out through analysis of protocols and records of patients with DM1 attended at this location from January to July 2017. The present study showed the patients with DM1 attended by CEAF / SESAPI, are predominantly teenagers and young adults, from the state capital. The survey showed that only 37% of DM1 patients have good glycemic control, showing a warning sign. It was shown that among the acute complications caused by DM1, hypoglycemia was the most frequent, in relation to chronic complications, 28% already had the same, with microalbuminuria being the most frequent. The prescriptions contained in the patients' protocols were analyzed and it was found that 42% of them were outside the requirements of the law, which can hinder the development of pharmacological therapy. Thus, it is possible to observe the importance of analyzing the pharmacoepidemiological profile of patients with DM1, as a relevant data for the discussion on the use of medications for DM1 patients of the CEAF / SESAPI specific to diabetics.